Sistem Monitoring Secara Real-Time Pencemaran Air Sungai Siak Pekanbaru Berbasis IOT - Fajar Syafrianda; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This research was aimed to indicate in real-time the level of water turbidity and heavy metals (zinc, lead and iron) concentration in water of Siak river by creating a prototype design of monitoring tools. The research was conducted from upstream and downstream of the Siak River at Rumbai Pesisir Sub-District Pekanbaru. The turbidity sensor and TDS EC Meter were used by the researcher to measure the level of water turbidity. The researcher also conducted some laboratory tests in order to get the data about heavy metal concentration in water. The results were converted into NTU (Nephelometric Turbidity Units) and were shown on the website and database in graphic form by using Internet of Thing (IoT). The findings of the research showed that the level of turbidity in water of Siak River was categorized as “Poor” This can be seen from the result in which the overall score was 90-120 NTU (Nephelometric Turbidity Units). Meanwhile, based on the laboratory test result, the heavy metal concentration showed there are some transformations in water of the Siak River. Keywords: Turbidity sensor, NTU (Nephelometric Turbidity Units), IoT, Siak River